Revealing the Legal Formal of Politization of Prophetic Hadith in Riyād al-Sālihin No. 1320: Menyingkap Legal Formal Politisasi Hadis Nabi dalam Riyād al-Sālihin No. 1320 - Amiruddin Priyatmaja, Ahmad (Jurnal Living Hadis, 2024)
The urgency of the Prophet's hadith often clashes with practical politics, so its meaning is no longer independent and is more directed towards individual and group interests. Indirectly, there is a reduction in meaning and purpose, so it is important to research this matter. In this paper, the researcher examines the hadith of the Prophet saw on riwayah of Imam Muslim no. 1320 in Riyād al-Sālihīn, to answer at least two problem formulations; 1). What is the formal legal form of hadith Muslim narration no. 1320 in Riyāḍ al-Ṣāliḥīnand 2). What is the form of politicization of hadith in practical political practice in the contemporary era. The method used is qualitative analysis, which is descriptive with a contextual-historical approach. The results of this study show that the hadith as the second holy text after the Qur'an has a strategic position in the belief of a Muslim and confirms the formal legal "prohibition" of politicizing hadith because it can urge the ralization of religious values.